Hydrochemical assessment of surface water in part of South-eastern Nigeria (2001)
"The area of study occurs mainly within the Calabar Flank and part of the adjacent basement terrain of the Oban Massif. The latter is composed of mainly migmatitic gneisses, phyllites, amphibolites, granites, schists and granodiorites, while the major lithologies of the Calabar Flank include carbonates, shales, claystones and sandstones. This study aims at determining the quality and usability of the water, in addition to ascertaining the possible pollutants and ways to ameliorate their effects. Results of some physical and hydrochemical parameters have average values of 5.53pH, 77.4mg/I TDS, 17.8mg/l Na+, 5.5mg/l Ca2+, 13.2mg/l Cl , 3.3mg/l S042', 0.7mg/I NO'3, and 49.6ms/cm conductivity. The water hardness and sodium absorption ratio (SAR) are respectively 20.5mg/l and fi.fi. The total hardness, Ca2+, S042' are higher for the water draining the carbonate rock environs, while the TDS, Na+, conductivity and Cl"" are greater in the basement rock areas. Hydrochemical parameters in the piper trilinear diagram, as well as the Gibbs plot, respectively suggest that the water is of sodium bicarbonate facies, and dissolved solids are mostly products of weathering. Application of R-mode factor analysis suggests that the main components of the water characteristics are related to hydrological, lithological and environmental controls. The factor containing CO32- and HCO3"", is derived from the carbonate rocks in the area, whereas Na+ and K+ which are possibly transported in solution as base exchange of clay minerals, notably characterize the basement rocks. The group showing enrichment in Cl , Mg2+ and NO3 is considered to be associated with environmental control, through precipitation of meteoric water, while the presence of S042"" is linkable to the aeration of sulfide minerals in the area. On the whole, the water is slightly acidic with low sodium hazard. It therefore satisfies the World Health Organisation (WHO) standards for domestic, agricultural and other industrial uses requiring usual treatment such as filtration and disinfection."